Obelia geniculata ... - Moura, Carlos J. (Zenodo, 2015)
Obelia geniculata (fig. 4I) Sertularia geniculata Linnaeus, 1758: 812. Obelia geniculata.— Hincks, 1868: 149, pl. 25 figs 1,1a.— Patriti, 1970: 35, figs 44, 44bis.— Cornelius, 1975a: 272, figs 1a–d, 5a–c.— Cornelius, 1982: 119 –120.—Cornelius, 1990: 550–557.— Vervoort, 1993: 558 –559.— Cornelius, 1995b: 301 –303, fig. 70.— Medel & López-González, 1996: 206.— Medel & Vervoort, 2000: 54 –58.—Peña Cantero & García Carrascosa, 2002: 162–163, fig. 31d.— Govindarajan et al., 2005: 213 –222, fig. 1. Laomedea geniculata.— Da Cunha, 1944: 61, fig. 35. Material studied. Ormonde, stn 4: fertile colonies, very abundant on the brown alga Laminaria ochroleuca Bachelot de la Pylaie; DBUA 1524.01. Remarks. Oceana (2005) reported an Obelia species, possibly corresponding to O. geniculata. The present manuscript confirms this species presence at the top of the Ormonde seamount. Reported distribution. Eastern Atlantic.—Widespread, from Iceland (Broch 1918) to South Africa (Millard 1975). Mediterranean.—Widespread ... : Published as part of Moura, Carlos J., 2015, The hydrozoan fauna (Cnidaria: Hydrozoa) from the peaks of the Ormonde and Gettysburg seamounts (Gorringe Bank, NE Atlantic), pp. 148-180 in Zootaxa 3972 (2) on pages 166-167, DOI: 10.11646/zootaxa.3972.2.2, http://zenodo.org/record/237108 ...